Website Interactivity In Malaysia And Australian Universities - Jano, Zanariah; Hussin, Hanipah; Abdullah, Aida Nasirah; Cheong, Kar Mee (CCSE, 2015)
The extent to which web sites in Malaysian and Australian universities project their interactivity level wasanalysed. Content analysis was employed to measure the interactivity level. Twenty-six guidelines were selectedand twenty university web sites from each country were randomly selected. The findings showed that human tomarketer and human to human showed significant difference while human to content did not show anydifference. This study will be an addition to web design literature and facilitate universities and individuals todevelop effective strategies to elevate the image of universities in the global context. Future study shouldexamine other interactivity dimensions which are not covered in this study and insights from web designer arealso deemed important to ascertain the scenario behind the screen.